Cultural, Morphological and Biochemical Variability Studies among the Isolates of Alternaria solani, the Causal Agent of Early Blight Disease of Tomato - Nagesh; Mushrif, S. K.; Sangeetha, C. G.; Reddy, T. B. Manjunatha; Kumar, J. S. Aravinda (International Journal of Bio-resource and Stress Management, 2021)
Present experiment was conducted at College of Horticulture, Bengaluru (KA) during year 2017–18 to study the cultural, morphological and biochemical variations among the isolates of the pathogen Alternaria solani, the causal agent of early blight disease in tomato. The results revealed variation among the isolates collected from different regions of Karnataka state, India with regard to the colony characteristics viz., colony colour, mycelial growth pattern, margin of the colony and zonations. Maximum mycelial growth in terms of diameter (90 mm) was observed in the isolates Bagalkot (BaBG) and Chikkamagaluru (CMH) on Czapek’s (Dox) agar medium while the least growth (36.33) was noticed in Bidar (BiHH) isolate. The isolate could grow better on Czapek’s (Dox) agar medium as among the 3 media tested Czapek’s (Dox) agar medium produced maximum growth of 80.70 mm and the least growth (63.70 mm) was noticed in V-8 juice agar. The morphological studies revealed that all the conidia of various isolates varied in length (25.07–42.90 µm), breadth (10.53–21.52 µm) and number of horizontal septa (2–7), longitudinal septa (0–4). Biochemical studies among the isolates revealed significant variation in their enzyme activities. The peroxidase activity was more in Chikamagaluru (CMH) isolate (81.80 Unit g-1 FW) least activity was found in Bidar (BiHH) isolate 11.78 Unit g-1 FW whereas the esterase activity was more Bengaluru (BYC) isolate (69.01 Unit g-1 FW) least activity was found in Bagalkot (BaBG) isolate 11.78 Unit g-1 FW. Existence of variation among the isolates of Alternaria solani isevident from the results obtained.